American Call For War : Cultural Reader Response To Ridley Scott's Black Hawk Down Movie (2001) - Safitri, Linda, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
The research's purpose is to reveal how the cultural reader response reflected in the Black Hawk Down movie. There are three objectives of the study; the first is to describe the dominant issues by the reviewers in applying reader response theory, second is to explain the background of the reviewer response to the movie and third is to explain the reasons that influenced American reviewer call for war to Somalia city. The dominant issue which is respond by the reviewers is the war movie dealing with the cultural reader response. This study is a qualitative study and using two data sources; they are primary and secondary data. The primary data source is the reviews of Black Hawk Down movie (2001) by Ridley Scott from IMDb (Internet Movie Database). The secondary data of this study are taken from other sources such as literary book, previous studies, articles, journals, and also website related to reader response theory. The outcome of the study shows the issue variation of cultural reader response. They are consisting of movie production, social, propaganda, military, politics, suffering, race and religion. The dominant of the issue variation is movie production.It consists of the elements of the movie that supported it such as; plot, director, actor, cinematography, acting, music, editing and etc. The word of American call for war it is taken from the story of the movie of Black Hawk Down. It is not taken from the political, propaganda, military and social issues. .